BIMBINGAN DAN PELATIHAN PEMANFAATAN MAKANAN SEHAT SEBAGAI IDE KREATIF USAHA KECIL - Rena Feri Wijayanti; Joni Dwi Pribadi; Yosi Afandi; Lina Budiarti; Musthofa Hadi (Publisher UPT P2M Politeknik Negeri Malang, 2017)
Creative ideas can come from anywhere and by making use of everything around us. Food is a common thing and become a basic necessity. Alternative business ideas can start from the use of food to be the main product in marketing in particular can be used for small businesses. The main purpose in the implementation of dedication is to provide information and knowledge and provide motivation that the form of creativity can start from simple things. Moreover, the creativity spirit can grow for all circles and not limited to age.